Impact of the FSRIA of 2002 on Texas agriculture - James D. Sartwelle; Steven L. Klose; Joe L. Outlaw; David P. Anderson; James W. Richardson (Texas A&M University, The Agricultural & Food Policy Center (AFPC), 2002)
The recently passed (and awaiting presidential signature) Farm Security and Rural Investment Act of 2002 includes many changes in current farm programs. The farm bill is expected to have a large impact on Texas producers' bottom lines. This report provides estimates of the impacts of the farm bill on Texas crop producers for the 2002-2003 crop year. These results should be considered preliminary. A full, in-depth study of the 2002 FSRIA is underway at this time. Results of that study should be available by early June. Producer returns are presented as coupled and decoupled returns. Coupled returns include market receipts and government payments in the form of loan deficiency payments or marketing loan gains. They are termed coupled because they are received for current production. Decoupled returns include counter-cyclical payments and direct (fixed or AMTA) payments. Producers are eligible for these payments regardless of whether they produce or not.
Keywords: 330